The Efficacy and Safety of Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor Combined With Thymosin in Advanced Non-Small Cell Lung Cancer Patients Harboring Active Epidermal Growth Factor Receptor Mutations - Feng, Yongdong; Zhu, Guangkuo; Lang, Song; Hao, Ping; Li, Guanghui; Chen, Fanglin; Zhuo, Wenlei; Duan, Yuzhong; Zhang, Anmei; Chen, Zhengtang; Sun, Jianguo (Frontiers in Oncology, 2021)
Objective: To explore the efficacy and safety of EGFR-TKI combined with thymosin therapy in advanced non-small cell lung cancer (NSCLC) patients harboring active EGFR mutations. Methods: Patients confirmed as advanced NSCLC with active EGFR mutations were recruited from August 2008 to July 2018 retrospectively. Patients treated with EGFR-TKI were classified as the EGFR-TKI group. And those received EGFR-TKI and thymosin therapy were designated as the EGFR-TKI plus thymosin group. The primary endpoint was progression-free survival (PFS). The secondary endpoints included overall survival (OS), tumor response and adverse effects. Results: The median PFS was significantly longer in EGFR-TKI plus thymosin group than that in EGFR-TKI group (14.4 months vs. 9.2 months; HR=0.433, 95% CI 0.322 - 0.582, P<0.0001 ). The median OS was also prolonged in EGFR-TKI plus thymosin group than that in EGFR-TKI group (29.5 months vs. 19.8 months; HR=0.430, 95% CI 0.319 - 0.580, P<0.0001 ). The objective response rate in EGFR-TKI plus thymosin group and EGFR-TKI group were 60.0% versus 60.8% (P=0.918). The disease control rate was 96.9% in EGFR-TKI plus thymosin group and 97.7% in EGFR-TKI group (P=1.000). There were no significant differences in adverse effects between the two groups. The number of CD3+T cells in peripheral blood decreased significantly after treatment including both CD3+CD4+T and CD3+CD8+T subsets in EGFR-TKI group, but not in EGFR-TKI plus thymosin group. Conclusions: Combination of EGFR-TKI and thymosin can significantly prolong the PFS and OS compared with EGFR-TKI monotherapy without more adverse events, which offers a new strategy in clinic.